Hubungan Pengetahuan Pola Makan dengan Faktor Risiko Penyakit Jantung pada Remaja - Febriana Rachmawati; Febri Nur Hidayah; Hendri Safitri; Tessalonika Ersaputri; Zahra Aulia Fauziah; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
This research analyzes the relationship between knowledge of dietary patterns and risk factors for heart disease in adolescents, especially students. The method used was quantitative with a cross-sectional design, involving 45 teenagers. The results show that the majority of respondents have low knowledge and negative dietary behavior, with p-value = 0.012, indicating a significant relationship. Knowledge of risk factors for heart disease is very important for establishing healthy eating behavior, which has an impact on future heart health.